1837 Miss. Laws 736-37, An Act To Prevent The Evil Practice Of Dueling In This State And For Other Purposes, § 5. - (:unkn) unknown (General Publisher, 1837)
Prohibited the use of any rifle, shotgun, sword cane, pistol, dirk, dirk knife, Bowie knife, or any other deadly weapon in a fight in which one of the combatants was killed, and the exhibition of any dirk, dirk knife, Bowie knife, sword, sword cane, or other deadly weapon in a rude or threatening manner that was not in necessary self-defense. Punishable by liability to decedent and a fine of up to $500 and imprisonment for up to 3 months.
--
Keywords: DUELING